Band Position‐Independent Piezo‐Electrocatalysis for Ultrahigh CO2 Conversion - Ma, Jiangping; Xiong, Xin; Wu, Di; Wang, Yang; Ban, Chaogang; Feng, Yajie; Meng, Jiazhi; Gao, Xingsen; Dai, Ji‐Yan; Han, Guang; Gan, Li‐Yong; Zhou, Xiaoyuan (Advanced materials (Weinheim), 2023)
Piezo‐electrocatalysis as an emerging mechano‐to‐chemistry energy conversion technique opens multiple innovative opportunities and draws great interest over the past decade. However, the two potential mechanisms in piezo‐electrocatalysis, i.e., screening charge effect and energy band theory, generally coexist in the most piezoelectrics, making the essential mechanism remain controversial. Here, for the first time, the two mechanisms in piezo‐electrocatalytic CO2 reduction reaction (PECRR) is distinguished through a narrow‐bandgap piezo‐electrocatalyst strategy using MoS2 nanoflakes as demo. With conduction band of −0.12 eV, the MoS2 nanoflakes are unsatisfied for CO2‐to‐CO redox potential of −0.53 eV, yet they achieve an ultrahigh CO yield of ≈543.1 µmol g−1 h−1 in PECRR. Potential band position shifts under vibration are still unsatisfied with CO2‐to‐CO potential verified by theoretical investigation and piezo‐photocatalytic experiment, further indicating that the mechanism of piezo‐electrocatalysis is independent of band position. Besides, MoS2 nanoflakes exhibit unexpected intense “breathing” effect under vibration and enable the naked‐eye‐visible inhalation of CO2 gas, independently achieving the complete carbon cycle chain from CO2 capture to conversion. The CO2 inhalation and conversion processes in PECRR are revealed by a self‐designed in situ reaction cell. This work brings new insights into the essential mechanism and surface reaction evolution of piezo‐electrocatalysis. Piezo‐electrocatalysis as an emerging mechano‐to‐chemistry energy conversion technique opens multiple innovative opportunities, drawing great interest but also suffering from the controversial mechanisms. A narrow‐bandgap piezo‐electrocatalyst strategy is proposed by choosing CO2 reduction as a probe reaction to distinguish the two potential mechanisms, i.e., screening charge effect and energy band theory, and reveal that piezo‐electrocatalysis is independent of band positions.